Universal synthesis and solar water evaporation application of covalent organic framework organic hydrogel

Through group protection strategy, COFs gels are constructed and conversion between different types of gels are achieved, which solves the problems of COF gel diversity and limited synthesis technology, and realizes high-performance COF gel materials, with wide industrial application prospects.

CN119859230APending Publication Date: 2025-04-22NANKAI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311361812.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The diversity and synthesis technology of existing covalent organic framework (COF) gels are limited, and their solvent interchangeability, frost resistance and formation mechanism have not been fully explored, which limits its wide application in industrial production and practical applications.

Method used

The COFs gel material was constructed in one-step by covalent linkage of imine by group protection strategy, and the conversion between organic hydrogel, organic gel and hydrogel was achieved through solvent exchange and freeze-drying.

Benefits of technology

It has achieved the characteristics of COFs gel with high crystallinity, high porosity, good mechanical properties, solvent properties and good frost resistance, and has a wide range of universality, and has shown good solar energy absorption, photothermal conversion and water transmission performance in the field of solar water evaporation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a universal, simple and extensible method for preparing the covalent organic framework gel by utilizing a plurality of group protection strategies. An amino monomer containing a protecting group and an aldehyde group monomer are subjected to aldehyde amine condensation to obtain a COF gel material, so that the non-melting COF can be formed. The prepared material has the characteristics of high crystallinity, high porosity, good mechanical property, good solvent property, good freezing resistance and the like, and the COF organic hydrogel can be very conveniently subjected to structure and function design, can easily load various functional groups, and has great industrial application value. The prepared organic hydrogel can be easily converted into hydrogel, organic gel and aerogel through solvent exchange and freeze drying, and the gap between different types of COF gels is broken through. The water transmission performance and the water transmission state are measured through a solar photo-thermal water evaporation experiment, and the COF hydrogel rich in azobenzene groups has good solar energy absorption, photo-thermal conversion and water transmission performance, is equivalent to the most advanced material and has a great industrial practical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of porous organic materials, and in particular relates to the universal synthesis of a class of covalent organic framework organic hydrogel materials and their application in the field of solar water evaporation. Background Art

[0002] Covalent organic frameworks (COFs), as an emerging class of crystalline porous polymer materials, have shown broad application prospects in separation, catalysis, optoelectronics, energy storage, drug delivery, water capture, and desalination due to their well-defined structures, customizable functions, adjustable pore sizes, high porosity, and high chemical and thermal stability. COFs may be ideal candidates for the preparation of COF gels for the following reasons. (I) The reactive monomers can be designed to control the reaction pathway and promote the formation of gels; (II) The rich topography of COFs can support bottom-up gel formation (e.g., COF fibers, COF nanosheets, and COF monoliths have the possibility of stepwise crosslinking within COF gels); (III) The rich functional groups in COFs promote the formation of gel networks (e.g., air stability, solvent stability, and pH stability). Currently, only a small number of COF gels have been reported, mainly used as aerogels and organogels for dye and oil-water separation, absorption of organic solvents, adsorption of iodine, and lithium-ion batteries. The development of COF organohydrogels remains underexplored. Moreover, the solvent interchangeability, antifreeze properties, and formation mechanism of COF gels have not been explored. Therefore, developing general, facile, and scalable strategies to prepare COF gels, especially organohydrogels, is crucial for the industrial production of COFs.

[0003] Gels are ubiquitous materials that initially spanned a variety of biological and non-biological systems but can now be extended to many technological applications and commercial products. Based on their fluid composition, gels can be mainly divided into organogels, hydrogels, organohydrogels, and aerogels. Among them, organohydrogels have attracted increasing attention due to their unique solvent exchangeability, antifreeze properties, water retention, tunable surface wettability, shape memory effect, and customizable functionalization. In addition, organohydrogels can bridge the gap between organogels and hydrogels, that is, organohydrogels can be transformed into hydrogels or organogels through solvent exchange, thus breaking the gap between different types of gels. Therefore, it is of great significance to develop new organohydrogels with high versatility. Although significant progress has been made in the development of organohydrogels and related devices, there are still many challenges to be addressed: (1) the diversity and synthesis technology of organohydrogels are still limited; (2) maintaining the structural integrity and solvent exchange resistance of organohydrogels is a challenge, which hinders their practical application. Therefore, the development of novel organohydrogels with good versatility and industrial applications is urgently needed.

[0004] According to the literature, the formation of organic hydrogels generally involves two processes. First, the polymerization process is initiated to produce long molecular chains. The regulation of the polymerization rate (for example, lowering the temperature and concentration, reducing the activity of the catalyst) is crucial in this process. Secondly, the long molecular chains are further cross-linked to form a network through chemical or physical effects such as hydrogen bonds. That is, the organic solvent forms clusters with water molecules through hydrogen bonds, and then the binary solvent is fixed by hydrogen bonds on the polymer chains, and finally an organic hydrogel network is formed. Therefore, a reasonable design principle is to design monomers / polymers containing hydrogen bond donor / acceptor groups, such as hydroxyl groups that can form hydrogen bonds, and to reasonably select organic solvents with hydrogen bond acceptor / donor groups, such as water, ethylene glycol, glycerol, etc. At the same time, it is necessary to adopt a synthetic strategy to slow down the reaction rate to provide opportunities for the effective construction of COF organic hydrogels. Summary of the invention

[0005] The purpose of the present invention is to adopt a universal group protection strategy to prepare COFs gel. This type of material has the advantages of high crystallinity, high porosity, good mechanical properties, good solubility and antifreeze properties, and can be very conveniently designed in structure and function.

[0006] Another purpose of the present invention is to measure the water transmission performance and water state through solar photothermal water evaporation experiments, and determine that the COFs organic hydrogel rich in azobenzene groups can achieve good solar energy absorption, photothermal conversion and water transmission performance, which is comparable to the most advanced materials and has great prospects for practical industrial applications. Other objects of the present invention will be apparent to those skilled in the art from the foregoing and following descriptions.

[0007] The first aspect of the present invention is to propose a universal group protection strategy for preparing COFs gel and realizing the conversion between organic hydrogel, organic gel and hydrogel through solvent exchange and freeze-drying methods. It is characterized in that the COFs gel material is constructed in one step by covalently linking imine using a group protection strategy.

[0008] Preferably, the synthesis method 1 is to directly add the group-protected di-linked and tri-linked amino monomers, the tri-linked monomers containing aldehyde groups and the catalyst into the reactor, condense the aldehyde amine under closed conditions to obtain the COFs gel material, and then wash and purify it.

[0009] Preferably, the monomer 1 is a group-protected di-linked and tri-linked amino monomer.

[0010] More preferably, the monomer 2 is a three-linked monomer containing an aldehyde group.

[0011] In a preferred embodiment of the present invention, the group-protected amino monomer is any one of benzyloxycarbonyl (Cbz)-protected, tert-butyloxycarbonyl (Boc)-protected, methyloxycarbonyl (Fmoc)-protected p-phenylenediamine, 4,4'-biphenylenediamine, p-diaminoazobenzene, 1,3,5-tris(4-aminophenyl)benzene, and 2,4,6-tris(4-aminophenyl)diazenyl)benzene-1,3,5-triol.

[0012] In a preferred embodiment of the present invention, the aldehyde monomer is any one of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde and 2-hydroxy-1,3,5-benzenetricarboxaldehyde.

[0013] Preferably, the catalyst is a compound containing an acidic functional group.

[0014] Further preferably, the catalyst is one of concentrated hydrochloric acid, concentrated sulfuric acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, and trifluoroacetic acid.

[0015] Preferably, the obtained COFs gel is an imine-linked COFs gel block.

[0016] Preferably, the pore size of the COFs material is 1.0-2.1 nm.

[0017] Preferably, the specific surface area of ​​the COFs material is 322-1625m 2 / g.

[0018] Preferably, the molar ratio of organic monomer 1 to organic monomer 2 is 3:2 or 1:1.

[0019] Preferably, in the reaction system, the amount of the catalyst acid used is 60-150 μL, more preferably 60 μL.

[0020] Preferably, in the reaction system, the amount of water used is 0.1-0.9 mL, more preferably 0.4 mL.

[0021] Preferably, the temperature of the reaction system is 120-150°C.

[0022] Preferably, in the reaction system, the solvent is o-dichlorobenzene, n-butanol, mesitylene, dioxane, tetrachloroethane, tetrahydrofuran, or n-heptane.

[0023] Preferably, the reaction time is 1-5 days, more preferably 3 days.

[0024] Preferably, the closed reaction vessel is a steel high-pressure reactor with a polytetrafluoroethylene lining.

[0025] The synthesis method of the present invention is to construct an imine-based COFs gel material through a group protection strategy, and the relevant general formula can be expressed as: In the general formula: The organic monomer 1 mainly includes: any one of benzyloxycarbonyl (Cbz) protected, tert-butyloxycarbonyl (Boc) protected, methyloxycarbonyl (Fmoc) protected p-phenylenediamine, 4,4'-biphenylenediamine, p-diaminoazobenzene, 1,3,5-tris(4-aminophenyl)benzene, 2,4,6-tris(4-aminophenyl)diazenyl)benzene-1,3,5-triol. The organic monomer 2 mainly includes: any one of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde and 2-hydroxy-1,3,5-benzenetricarboxaldehyde. The monomers 1 and 2 mentioned above can be combined arbitrarily, and the target COFs can be prepared under any one of the conditions under which a catalyst is involved. The catalyst is any one of concentrated hydrochloric acid, concentrated sulfuric acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, and trifluoroacetic acid.

[0026] Preferably, the solvents selected for the solvent resistance and gel conversion include water, seawater, aqueous solutions with pH=0 and pH=12, and different organic solvents, including DMF, CH2Cl2, CHCl3, THF, n-hexane, toluene and acetonitrile.

[0027] Preferably, the conditions selected in the antifreeze property include the antifreeze property of COF gels with different water contents at -20 and -40°C.

[0028] Preferably, the photothermal conversion performance of the COFs gel solar evaporator is a simulated sunlight intensity (1 kW / m 2 ) under irradiation.

[0029] Further preferably, in the test of the photoisomerization behavior of the azo groups in NKCOF and TpAzo in the COFs gel solar evaporator, under 365nm and 440nm light, the azo groups of the four COF materials did not show any photoisomerization behavior but generated heat energy, causing the solar evaporator to quickly heat up to 65-80°C.

[0030] Preferably, in the actual evaporation enthalpy test of water in COF gel, the flow rate is 50 mL / min under N2 atmosphere.

[0031] Preferably, the heating rate is 5°C / min.

[0032] Preferably, the heating range is from 25 to 180°C.

[0033] Preferably, in the COF gel water adsorption performance test, the sample is degassed at 120° C. for 24 h. Compared with the prior art inventions, the present invention has the following innovations: 1. For the first time, the group-protected amino monomer was used as the building block of imine-based COFs, successfully realizing the universal synthesis of COF gels, greatly improving the formability of COFs. The prepared organic hydrogel can be easily transformed into hydrogel and organic gel through solvent exchange and freeze drying, breaking the gap between different types of COF gels and having a wide range of universality. 2. For the first time, a COFs gel rich in azo groups using a group protection strategy is provided, which has good solar absorption, photothermal conversion and water transport properties, comparable to the most advanced materials, and has great prospects for practical industrial applications. Description of the drawings:

[0034] Figure 1 : The present invention is used to construct a group protection strategy monomer structure formula and a COF gel structure formula of a covalent organic framework gel material.

[0035] Figure 2 : Schematic diagram of the synthesis route of the covalent organic framework gel material prepared by the present invention.

[0036] Figure 3 : Powder diffraction pattern of a representative covalent organic framework gel material prepared in the present invention.

[0037] Figure 4 : Infrared spectrum of a representative covalent organic framework gel material prepared by the present invention.

[0038] Figure 5 : 77K nitrogen isothermal adsorption-desorption curve of the representative covalent organic framework gel material prepared by the present invention.

[0039] Figure 6 : Photos of volume changes of representative covalent organic framework gel materials prepared by the present invention before and after treatment in different solvents.

[0040] Figure 7 : Compression-stress curves of TpPa COF organohydrogel after treatment in different solvents.

[0041] Figure 8 : PXRD curves of TpPa COF organohydrogel after treatment in different solvents.

[0042] Fig. 9 : FT-IR curves of TpPa COF organohydrogel after treatment in different solvents.

[0043] Fig.10 : Antifreeze test diagram of the representative covalent organic framework gel material prepared by the present invention.

[0044] Fig.11 : Diagram of a solar thermal water evaporation device using a representative covalent organic framework hydrogel material prepared by the present invention.

[0045] Fig.12 The representative covalent organic framework hydrogel material prepared by the present invention is subjected to the simulated solar light intensity (1kW / m 2 ) device and saturated water absorption and water transmission rate.

[0046] Fig.13 : Water contact angle of representative covalent organic framework hydrogel materials prepared in the present invention.

[0047] Fig.14 : A graph showing the change in mass of pure water used for photothermal evaporation using a representative covalent organic framework hydrogel material prepared by the present invention over time.

[0048] Fig.15 : Long-term stability test diagram of pure water photothermal evaporation of the representative covalent organic framework hydrogel material NKCOF-61 prepared by the present invention.

[0049] Fig.16 : Long-term stability test diagram of seawater photothermal evaporation of the representative covalent organic framework hydrogel material NKCOF-61 gel prepared by the present invention.

[0050] Fig.17 : A diagram showing changes in ion concentration of a representative covalent organic framework hydrogel material prepared by the present invention before and after seawater desalination.

[0051] Fig.18 : SEM image of the representative covalent organic framework hydrogel material prepared in the present invention after evaporation.

[0052] Fig.19 : FT-IR graphs of representative covalent organic framework hydrogel materials prepared in the present invention before and after evaporation.

[0053] Fig. 20 : PXRD patterns of representative covalent organic framework hydrogel materials prepared in the present invention before and after evaporation. Specific implementation method: Unless otherwise specified in the context of this application, the technical terms and abbreviations used in this application have the conventional meanings known to those skilled in the art; unless otherwise specified, the raw material compounds used in the following examples are commercially available. Example 1 is a synthesis method of the material, Example 2 is a solvent exchange test of the material, Example 3 is a test of the antifreeze property of the material, and Example 4 is a test of the representative material on solar thermal seawater evaporation.

[0054] According to the present invention, the general synthesis of a class of covalent organic framework organic hydrogel materials and the relevant performance characterization tests of their applications in the field of solar water evaporation are described in detail below. On the contrary, the following examples are only used to further explain and invent the present invention and should not be considered as limiting the scope of the present invention.

[0055] Embodiment 1: According to the above general formula, weigh one of benzyloxycarbonyl (Cbz) protected, tert-butyloxycarbonyl (Boc) protected, methyloxycarbonyl (Fmoc) protected p-phenylenediamine (0.09 mmol), 4,4'-biphenylenediamine (0.09 mmol), p-diaminoazobenzene (0.09 mmol), 1,3,5-tris(4-aminophenyl)benzene (0.06 mmol), 2,4,6-tris(4-aminophenyl)diazenyl)benzene-1,3,5-triol (0.06 mmol), 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (0.06 mmol, 12.60 mg), 2,4-dihydroxy-1,3,5-pyromellitic acid trimesic acid (0.06 mmol, 11. 60mg), 2-hydroxy-1,3,5-benzenetricarboxaldehyde (0.06mmol10.60mg), add 4mL of o-dichlorobenzene, n-butanol, mesitylene, one or more of dioxane, tetrachloroethane, tetrahydrofuran, n-heptane, and one of concentrated hydrochloric acid (60μL), concentrated sulfuric acid (30μL), p-toluenesulfonic acid (140mg), trifluoromethanesulfonic acid (60μL), and trifluoroacetic acid (60μL), carefully put into a steel high-pressure reactor with a polytetrafluoroethylene liner, put it in a 120℃ oven to react for 3 days, and a dark reddish brown to black COF gel is obtained after the reaction. After soaking it in DMF and CH3OH, Soxhlet extraction is continued in THF for 48h, followed by solvent exchange. like Figure 3 As shown in Figure 2, the powder X-ray diffraction pattern shows that the synthesized COFs material has high crystallinity. Figure 4 Infrared spectroscopy test further proved that the material is an imine-linked COFs material, where 1571 cm -1 The characteristic peak at 2 corresponds to the stretching vibration of the carbon-oxygen double bond of enol tautomerism. Figure 5The isothermal nitrogen adsorption-desorption curve of TpPa gel material at 77K, and its BET surface area is 901m 2 / g, pore size is 1.2nm.

[0056] Example 2: The freshly prepared TpPa COF organohydrogel was immersed in water, seawater, aqueous solutions of pH=0 and pH=12, and different organic solvents, including DMF, CH2Cl2, CHCl3, THF, n-hexane, toluene and acetonitrile, for two weeks to obtain hydrogels and organogels. The gels were able to maintain their intact shape, with almost no change in volume, and had good solvent resistance. Figure 6 Photos showing the volume change of the representative covalent organic framework gel material TpPa COF organohydrogel prepared in the present invention before and after treatment in different solvents. Figure 7 The compression-stress curves of TpPa COF organohydrogels treated in different solvents are shown in Figure 2. Figure 8 As shown in Figure 2, the powder X-ray diffraction pattern shows that the COFs gel material does not lose its crystallinity after solvent exchange. Fig. 9 As shown, Fourier transform infrared spectroscopy shows that the COFs gel material still has good chemical stability after solvent exchange.

[0057] Example 3: Freshly prepared TpPa COF gels with water contents ranging from 0% to 100% were placed under antifreeze test conditions at -20 and -40°C. Fig.10 As shown in the figure, at -20°C, COF gels with a water content below 25% did not freeze, maintaining good antifreeze properties. When the temperature dropped to -40°C, COF gels with a water content greater than 15% began to freeze on their surface. In general, COF organohydrogels have good antifreeze properties.

[0058] Example 4: The COF gel prepared in Example 2 was subjected to sufficient water exchange to ensure that no organic solvent was present, and then used for solar water evaporation performance testing. Fig.12 As shown in the figure, PS foam is placed on the upper part of a beaker filled with a certain amount of water as a support and insulation layer, and a cotton core is added in the middle of the PS foam for the channel of water upward transmission. COF gel is placed on the top and placed at 1kW / m 2 The simulated sunlight is exposed to Fig.13 As shown in Figure 2, the saturated water absorption and water transmission rate of NKCOF-61 gel both showed the highest values. Fig.14 As shown in Figure 2, different COF gels all show hydrophilic properties. Figure 15-20 As shown, NKCOF-61 gel material has fast water transmission speed, excellent long-term structural and chemical stability, and excellent long-term use stability.

[0059] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention in any form. Any researcher and technician familiar with the field, without departing from the scope of the technical solution of the present invention, using the above content to make non-innovative changes and modifications to the technical solution of the present invention, such as only changing the addition ratio of raw materials and reagents, reaction time and operation process, etc., should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogel based on a covalent organic framework material, characterized in that: Directly add di-linked and tri-linked amino monomers containing protective groups, tri-linked monomers containing aldehyde groups and catalysts into a reactor, and condense aldehyde amines under closed conditions to obtain COFs gel material; The protecting group is an amino protecting group; the amino monomer is an organic molecule containing an amino group; the aldehyde monomer is an organic molecule containing an aldehyde group; and the catalyst is a compound containing an acidic functional group.

2. The method according to claim 1, characterized in that The amino monomer is selected from any one of p-phenylenediamine, 4,4'-biphenylenediamine, p-diaminoazobenzene, 1,3,5-tris(4-aminophenyl)benzene, and 2,4,6-tris(4-aminophenyl)diazenyl)benzene-1,3,5-triol; and the protecting group is selected from one or more of benzyloxycarbonyl (Cbz), tert-butyloxycarbonyl (Boc), and methyloxycarbonyl (Fmoc).

3. The method according to claim 1, characterized in that The aldehyde-containing three-linked monomer is any one of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde, and 2-hydroxy-1,3,5-benzenetricarboxaldehyde.

4. The method according to claim 1, characterized in that The catalyst is selected from one or more of concentrated hydrochloric acid, concentrated sulfuric acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, and trifluoroacetic acid.

5. The method according to claim 1, characterized in that The reaction solvent is selected from one or more of o-dichlorobenzene, n-butanol, mesitylene, dioxane, tetrachloroethane, tetrahydrofuran and n-heptane.

6. The method according to claim 1, characterized in that The method also includes the steps of washing the COFs gel material with an organic solvent and drying the COFs gel material.

7. A hydrogel based on a covalent organic framework material prepared by the method according to any one of claims 1 to 6, characterized in that: The hydrogel is a hydrogel block connected by imine groups.

8. The hydrogel according to claim 7, characterized in that The pore size of the hydrogel is 1.0-2.1 nm.

9. The hydrogel according to claim 7, wherein the structure of the COFs repeating unit is: Where "..." represents a repeating unit.

10. Use of the hydrogel according to any one of claims 7 to 9, characterized in that The hydrogel is used for solar energy absorption, photothermal conversion or water transport.

Citation Information

Cited By

  • Photoresponse azobenzene covalent organic framework material and preparation method thereof

    CN120554598A